SmallVDM: An Environment for Formal Specification and Prototyping in Smalltalk - Meira, Silvio Lemos; Santos, Cássio Souza dos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1991)
We present an environment for specification and prototyping of object-oriented systems in Smalltalk along with a style of specification, which allows the definition of some object-oriented characteristics in VDM. A set of auxiliary tools stimulates the development of specifications on-line and fast prototyping. The presentation is mostly informal and the mechanism is exemplified by giving an object-based specification of a simple process scheduler. We discuss the gains of using formal methods, coupled with a good programming environment, in the implementation of object-oriented software systems.